In Search of the Key to the Theology of Paul the Apostle - Rakocy, Waldemar (Collectanea Theologica, 2021)
The Author of the paper looks for a key to the theological thought of the Apostle Paul. The fact that it lacks a clear definition results in authors radically differing in their perception, for instance, regarding the relationship between the Old and the New Testament, and as a result, whether or not the Old Testament has a decisive influence on the Pauline thought, continuing along this line: whether the Apostle in his view always remained a Jew, or whether he distanced himself from Judaism. The fact that we do not have a category clearly defining the relationship between the Old and New Testament salvific reality results in an abundance of contradictory opinions. That is also transferred to other areas of the Pauline theology. The interpretation of Paul’s theology tends to be determined by preconceptions, built upon various ways of understanding the significance of the Old Testament, or various relationship to Judaism and its thought. The author of the paper indicates a concept, treated as marginal by scholars, of a new creation in Christ as the key to understanding the Pauline thought. It lays in the background of all themes treated by Paul and connects them into a single, coherent entity.